Brasil periferia(s): a comunicação insurgente do Hip-Hop - Moassab, Andreia (2008)
This thesis studies the resistance processes carried out in Brazil by thousands of young people linked to hip-hop. These youngsters actively participate in the production of knowledge and in the re-semantization of the Brazilian deprived suburbs in the context of the contemporary world. Their voice emerges against homogenized symbolic constructions produced by dominant thinking, i.e., that strand of thought grounded on values and desires in strict accordance with the hegemonic economic system. We understand that the sharing of knowledge is the basis for resistance. Therefore, comunication is placed at the core of resistence: knowledge shared and multiplied. The concept of comunication, however, has been increasingly limited to mediatic objects. As a consequence, diverse communicative practices are being neglected in communication epistemological theory. This is why it is extremely important to widen the understanding of communicational objects in order to include manifestations otherwise invisible in mainstream media. The analytical corpus of this investigation is composed by the lyrics of hip-hop songs, analysed from the point of view of comunication and sociology. One of the main theoretical landmarks in this work are the concepts from Boaventura Santos (2006a): ecology of knowledge, sociology of absence and sociology of emergence. Fundamental texts regarding power, resistence, empowerment and emancipation in the text were: Foucault (1979; 1988; 2000), Santos (2005a; 2006a; 2006b; 2007a) and feminist thought, especially Magdalena León (2000) and Patrícia Collins (1991). In the comunication field, we have made extensive use of the work by José Luiz Aidar Prado (2006a; 2006b) and Muniz Sodré (2002), as well as Hannah Arendt s writings (2007) in political philosophy. The discussions on globalization were carried out from the perspective of Milton Santos (2001) and again Boaventura Santos (2002), as well as Zizek`s (2006) criticism of multiculturalism, in order to establish a relationship between globalization, local cultures and resistence. Specific points on our investigation demanded specialized approaches such as urban planning; social movements; racial relations; urban violence; police violence; criminal control and human rights; critical criminology; identity; gender; and oral culture. We conclude the text pointing out that hip-hop is an active actor in the construction of an insurgent communication. Such insurgent comunication is able to symbolically reorder aspects misrepresented by hegemonic media concerning black and poor people living in the suburbs. Therefore, hip-hop as counter-hegemonic pratices constitutes a critical action able to deconstruct naturalizing visions on cultures